Constraining Glacial Isostatic Adjustment with Horizontal GPS Velocities in Antarctica - Hermans, Tim (author) (2017)
Glacial isostatic adjustment is the viscoelastic response of the Earth to ice and ocean loads. In forward models of glacial isostatic adjustment, mantle viscosity is often assumed to be laterally homogeneous. However, a lateral transition in shear wave velocities suggests a sharp transition in viscosity between West and East Antarctica. Along this transition, horizontal GPS velocities of ANET/POLENETWest of the Ross Sea Embayment point towards the ice load rather than away from it. It is unclear why, as the dependency of horizontal velocities on viscosity is not well understood. In this thesis, this dependency is clarified, and it is investigated with a 3D finite-element model if the horizontal GPS velocities can be used to constrain the viscosity transition. It was found that horizontal velocities point away from the ice load for viscosities of 1020 Pa s and lower, whereas for 1021 Pa s and higher their direction is reversed. The results in this thesis show that the GPS measurements at the Ross Sea Embayment likely require a lateral viscosity transition. Preferred viscosities in the upper mantle are found to lay between 1018 and 1019 Pa s at the West Antarctic side of the transition, and between 1021 and 1022 Pa s at the East Antarctic side. The results demonstrate that horizontal GPS velocities can be used to constrain lateral variations in rheology. As more studies will start to use 3DEarth models, horizontal GPS velocities should be used as one of the primary constraints of glacial isostatic adjustment, since their direction can be reversed depending on mantle viscosity. Aerospace Engineering | Astrodynamics & Space Missions